The use of RemoweLL oxygenator-integrated device in the prevention of the complications related to aortic valve surgery in the elderly patient: Preliminary results. (29th August 2020) - Molardi, Alberto; Di Chicco, Maria V; Carino, Davide; Goldoni, Matteo; Ricci, Matteo; Borrello, Bruno; Gripshi, Florida; Gherli, Tiziano; Nicolini, Francesco
Abstract: Background: The effects of fat microembolization due to cardiopulmonary bypass are well known in cardiac surgery. Our aim is to evaluate the use of the RemoweLL device (Eurosets, Medolla, Italy) during elective aortic valve replacement in elderly patients (>70 years old) to rate its biochemical and clinical effects. The RemoweLL device is an oxygenator-integrated reservoir which combines two strategies for fat emboli and leucocytes removal: filtration and supernatant elimination. Methods: Forty-four elderly patients were enrolled and assigned randomly to a Group A (standard device) and a Group B (RemoweLL). Biochemical effects were evaluated by blood samples, which were tested for white blood cells, neutrophils, protein SP-100 and interleukin 6 besides standard lab tests. Our clinical endpoints were any type of neurological, cardiac, respiratory, gastrointestinal or renal complications, and length of stay in the intensive care unit. Statistical analysis was carried out with chi square test for non-parametric data; t test and analysis of variance for repeated measures were used for parametric data. Results: Group B showed lower levels of white blood cells, neutrophils, interleukin 6 and protein SP-100 immediately and 24 hours after the operation. Group B also showed a lower amount of neurocognitive type II dysfunction even if the length of stay in the ICU did not change. Conclusions: The RemoweLL system is safe and effective in reducing inflammatory response to cardiopulmonary bypass and it could be a useful tool in minimizing negative effects of cardiopulmonary bypass; however, it does not seem to have any effect on elderly patients' hospital stay.